2020
DOI: 10.1155/2020/3730657
|View full text |Cite
|
Sign up to set email alerts
|

The Search of miRNA Related to Invasive Growth of Nonfunctioning Gonadotropic Pituitary Tumors

Abstract: Purpose. Nonfunctioning gonadotropic pituitary neuroendocrine tumors (PitNETs) are among the most frequent neoplasms of pituitary gland. Although PitNETs are commonly considered benign, a notable part of patients suffer from tumor recurrence after treatment. Invasive growth of pituitary tumor is among the most important prognostic factors. Since molecular features of invasiveness are of potential clinical usefulness, this study was aimed to verify whether invasive and noninvasive nonfunctioning gonadotropic Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the field of PA research, several reports have confirmed that the abnormal expression of multiple miRNAs is associated with the occurrence and progress of PA [11]. For example, recent studies found that the 14q32 cluster-encoded miRNAs were downregulated in PA [13]; differential expression of hsa-miR-185-5p was confirmed in the validation cohort between invasive and noninvasive gonadotropin secreting PA [14]; miRNA-7a2 regulates prolactin production in ACTH-PA cells [15]. Therefore, miRNAs may play an important role in the pathogenesis of PA and may be used as molecular biomarkers for the early diagnosis of PA and can also provide new ideas for the treatment of PA.…”
Section: Mirna-involved Mechanisms In Pa Pathologymentioning
confidence: 99%
“…In the field of PA research, several reports have confirmed that the abnormal expression of multiple miRNAs is associated with the occurrence and progress of PA [11]. For example, recent studies found that the 14q32 cluster-encoded miRNAs were downregulated in PA [13]; differential expression of hsa-miR-185-5p was confirmed in the validation cohort between invasive and noninvasive gonadotropin secreting PA [14]; miRNA-7a2 regulates prolactin production in ACTH-PA cells [15]. Therefore, miRNAs may play an important role in the pathogenesis of PA and may be used as molecular biomarkers for the early diagnosis of PA and can also provide new ideas for the treatment of PA.…”
Section: Mirna-involved Mechanisms In Pa Pathologymentioning
confidence: 99%
“…Boresowicz et al [ 40 ] investigated whether a miRNA signature could discriminate NFPA patients with invasive and noninvasive gonadotropic pituitary neuroendocrine tumors (PitNETs), one of the most frequent histopathological subtypes of NFPAs. Comparing miRNome by using next generation sequencing (NGS) and by applying receiver operating characteristics (ROC) curve analysis for the 29 identified differentially expressed miRNAs, the authors found six miRNAs (miR-184, miR-181a-2-3p, miR-93-3p, miR-574-5p, miR-185-5p, and miR-3200-5p) that could be potential biomarkers of invasiveness.…”
Section: Mirnas In Non-functioning Pasmentioning
confidence: 99%